(untitled) (Mustansiria Dental Journal, 2005)
A deaf child from birth has experienced disturbed leaming which affect his/her intellectual skills, social environment and emotional relation ship. There fore this oral health survey was conducted among 519 deaf persons and 532 students aged 61-5 years in the middle region of Iraq (Baghdad, Anbar, Diyala, Salah AlDeen , Bayblon and Kerbala). The purpose of this study was to investigate and compare the oral health status and treatment needs of deaf persons and students in the same geographical area. Results showed that 40.66% of deaf persons were caries free compared to schools students 33.46%; dmfs mean value of deaf persons was found to be lower (3.935 :l: 0.312) than that of students (4.252 dc 0,277) while DMF S mean value in deaf persons was higher (0.763 1 0.095) than that recorded in students (0.603 )080.6 6 with no statistically significant difference. Higher percentage of deaf person and schools students were found in need of two or more surface restoration 30.44% , %30804 respectively. Deaf persons demonstrated a higher mean plaque index value 68051( t 0.012) and gingival index value (1.098 i 0.914 i 0.012) respectively, so efforts should be made to ensure access to preventive care .